The Analysis of Swear Words in Suicide Squad Movie - Fahmi Shifa' Ushudur; M. Bahri Arifin; Famala Eka Sanhadi Rahayu (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Swear words as a strong language that is expressed by a person to their powerful emotion by Swan in 1995. The present study discussed the type and the function of swear words in Suicide Squad movie. This research is descriptive qualitative study whose data are in the form of utterances uttered by the characters in Suicide Squad movie that shown the types of swear words and their functions. In finding, the researcher found five types of swear words in Suicide Squad movie. Those are dysphemism, idiomatically, abusively, emphatically and cathartically. The researcher also founds the functions those of swear words as they functioned as showing anger or frustration, descriptive- evaluative, joke, surprise and sarcastic irony. The findings showed that abusive was the dominant type, because this type was mostly used by the characters in Suicide Squad movie. The implication of this research is knowing that swear words found in Suicide Squad movie showed that the characters in Suicide Squad movie used swear words not always to humiliate others or to express anger, but also to express their other emotions and to show friendliness.